The Relationship Between Constructivist Thinking and Academic Engagement Among University Students in Light of Some Variables - Egbaria, Mohamad Mostfa (European Scientific Journal, ESJ, 2024)
The current study aims to reveal the relationship between constructivist thinking and academic engagement among university students in light of some variables. To achieve the objectives of the study, a sample of 697 male and female students was selected at the Qasimi Academic College of Education within the Green Line in the Arab city of Bouqa ’a, where they were selected in the available sample manner. The constructive thinking scale and measure of academic participation were applied. The results showed a statistically significant positive correlation between academic participation and constructive thinking dimensions, while the results showed a statistically significant negative correlation between academic participation and destructive constructive thinking dimensions. The results indicated that there were no significant differences in correlation factors between constructive thinking and academic engagement attributed to gender and specialization.